2010
DOI: 10.1158/1535-7163.mct-09-0508
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolutionary Analysis of Cancer Cell Lines

Abstract: With genome-wide cancer studies producing large DNA sequence data sets, novel computational approaches toward better understanding the role of mutations in tumor survival and proliferation are greatly needed. Tumors are widely viewed to be influenced by Darwinian processes, yet molecular evolutionary analysis, invaluable in other DNA sequence studies, has seen little application in cancer biology. Here, we describe the phylogenetic analysis of 353 cancer cell lines based on multiple sequence alignments of 3,25… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Gymnopoulos and co-workers mapped H1047R/L mutations onto a structural model of PIK3CA which suggested that these changes are located near the hinge region of the activation loop and could serve to increase catalytic activity [28]. Given the importance of mutated kinases in tumor cell viability and their increased exploitation as cancer drug targets, better insights into delineating between passenger and driver mutations might be gained through broader sequence comparisons across different species as well as related protein family members [29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…Gymnopoulos and co-workers mapped H1047R/L mutations onto a structural model of PIK3CA which suggested that these changes are located near the hinge region of the activation loop and could serve to increase catalytic activity [28]. Given the importance of mutated kinases in tumor cell viability and their increased exploitation as cancer drug targets, better insights into delineating between passenger and driver mutations might be gained through broader sequence comparisons across different species as well as related protein family members [29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, a ranked list of the top ~1000 genes was assembled with mutations affecting protein function relevant to cancer [41]. A variety of additional approaches have been implemented to uncover drivers by, for example, integrating copy-number variation and gene expression [31] and phylogenetic analysis [23,42]. …”
Section: Identifying Causal Genetic Eventsmentioning
confidence: 99%
“…The table covers proteins associated with a variety of diseases ranging from pancreatic cancer, epilepsy, and to carpal tunnel syndrome. Beside the OMIM evaluations, SNPs reported in various cancer lines were tested [31] for their position relative to domains and domain altering potential. Out of 13 unique SNP IDs presented in Table 2 of Zhang [31], one was found in the PROSITE domain region, and it corresponded to a domain-altering SNP associated with pancreas cancer.…”
Section: Resultsmentioning
confidence: 99%